2006
DOI: 10.1007/s00439-005-0124-7
|View full text |Cite
|
Sign up to set email alerts
|

A SALL4 zinc finger missense mutation predicted to result in increased DNA binding affinity is associated with cranial midline defects and mild features of Okihiro syndrome

Abstract: Truncating mutations of the gene SALL4 on chromosome 20q13.13-13.2 cause Okihiro and acro-renal-ocular syndromes. Pathogenic missense mutations within the SALL4 or SALL1 genes have not yet been reported, raising the question which phenotypic features would be associated with them. Here we describe the first missense mutation within the SALL4 gene. The mutation results in an exchange of a highly conserved zinc-coordinating Histidine crucial for zinc finger (ZF) structure within a C2H2 double ZF domain to an Arg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 30 publications
0
43
0
Order By: Relevance
“…The zinc finger domains are essential for SALL4 function since deletions or non-sense mutations lead to developmental disorders (14, 30 -32). In fact, a mutation with histidine (His-888 in SALL4A corresponding to His-451 in SALL4B) changed into arginine within the double zinc finger domain is associated with Okihiro syndrome in human (33). Lys-401, a crucial residue for sumoylation, also lies in close proximity to the second phosphorylation site, suggesting a possible regulatory interaction between these residues.…”
Section: Sall4b Is Post-translationally Modified-sall4mentioning
confidence: 99%
“…The zinc finger domains are essential for SALL4 function since deletions or non-sense mutations lead to developmental disorders (14, 30 -32). In fact, a mutation with histidine (His-888 in SALL4A corresponding to His-451 in SALL4B) changed into arginine within the double zinc finger domain is associated with Okihiro syndrome in human (33). Lys-401, a crucial residue for sumoylation, also lies in close proximity to the second phosphorylation site, suggesting a possible regulatory interaction between these residues.…”
Section: Sall4b Is Post-translationally Modified-sall4mentioning
confidence: 99%
“…Mutations of SALL4 gene have been detected in patients with several developmental disorders, and these mutations either occur in the transactivation domain or cause premature translational termination. 12,41,42 To date, no mutations have been reported that reside in the nuclear localization domain. It is likely that this type of mutations may severely disrupt the function of SALL4, thus leading to embryonic lethality.…”
Section: 39mentioning
confidence: 99%
“…Some OS patients also show severe growth retardation, also seen in patients affected by TBS that might indicate pituitary dysfunctions associated with SALL4 mutations (Kohlhase et al, 2005;Miertus et al, 2006). A plausible explanation for the features shared by OS and TBS is that SALL4 can interact with SALL1.…”
Section: Sall Genes In Diseasementioning
confidence: 99%